Multi-Trophic Species Interactions Shape Seascape-Scale Coral Reef Vegetation Patterns - Madin, Elizabeth M. P.; Precoda, Kristin; Harborne, Alastair R.; Atwood, Trisha B.; Roelfsema, Chris M.; Luiz, Osmar J. (Frontiers in Ecology and Evolution, 2019)
How species interactions shape habitat structure is a longstanding question in ecology. A curious phenomenon reflecting ecological self-organization around reef habitat structures exists on coral reefs: large-scale (hundreds to hundreds of thousands of m2) halo-like patterns surrounding patch reefs, i.e., individual coral reefs that are often separated by seagrass or macroalgal meadows. These ‘halos’, long known to occur in various locations worldwide, reflect a distinct band of unvegetated sediments surrounding coral patch reefs. However, the full suite of mechanisms controlling them have never been rigorously explored, perhaps due to the common assumption dating back nearly fifty years that they arise solely from reef-based herbivory patterns shaped by anti-predator behavior. Here we provide empirical evidence from a set of halos within Australia’s Great Barrier Reef that risk-averse foraging and a previously unrecognized functional group contribute to halo formation, demonstrating that these halos cannot be explained by any one mechanism in isolation. Our results show that halos are a more complex ecological phenomenon than previously assumed by the majority of studies of halos. Specifically, risk-averse grazing by herbivores is likely a key mechanism behind the formation of halos, as generally assumed, but bioturbators also play a central role. This knowledge furthers our understanding of how small-scale species interactions can structure habitat at landscape scales. These large-scale habitat features are important because they affect at least one important ecosystem function, carbon storage, and potentially others (e.g., biological nutrient transfer). These results also raise the question of whether other self-organized ecological patterns may be more nuanced than is currently assumed. This study capitalizes on recent advances in high resolution satellite imagery accessibility that allow ecologists to measure landscape-scale habitat features nearly everywhere on land and in shallow seas. Our results suggest that halos may hold potential as the basis for a tool for remotely observing ecological interactions and measuring large-scale ecosystem change on coral reefs.